Perancangan Jaringan Fiber To The Home (FTTH) Link STO Arengka Ke Perumahan Villa Melati Permai II - Widyantoro Tejo Mukti; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Villa Melati Permai I has equipped by FTTH (Fiber to the Home) network facility, later on the villa melati Permai I has been extended into villa melati permai II, in this villa melati permai II has not been equipped by FTTH facility. This paper, proposes to design villa melati permai II FTTH network according to parameter standard of Villa Melati Permai I equipment. The analysis parameters containing Link Power Budget, Rise Time Budget and BER for permormance system that simulated by OptySystem. From the calculations of link power budget, the total attenuation result is 21,35 dB for downstream and 22,13 dB for upstream. The loss of receiver result is -19,85 dBm for downstream and -20,63 dBm for upstream. For system performance parameters are generated from the simulation BER OptiSystem, BER values obtained 1,64